Effectiveness and (in)efficiencies of compensation regulation: Evidence from the EU banker bonus cap - Stefano Colonnello; Michael Koetter; Konstantin Wagner (Halle Institute for Economic Research (IWH), 2020)
We investigate the (unintended) effects of bank executive compensation regulation. Capping the share of variable compensation spurred average turnover rates driven by CEOs at poorly performing banks. Other than that, banks' responses to raise fixed compensation sufficed to retain the vast majority of non-CEO executives and those at well performing banks. We fail to find evidence that banks with executives that are more affected by the bonus cap became less risky. In fact, numerous results indicate an increase of risk, even in its systemic dimension according to selected measures. The return component of bank performance appears to be unaffected by the bonus cap. Risk hikes are consistent with an insurance effect associated with raised the increase in fixed compensation of executives. The ability of the policy to enhance financial stability is therefore doubtful.
urn:nbn:de:101:1-2018080614481225730023
Keywords: G21; G32; G34; 330; banks; bonus cap; executive compensation; executive turnover